Effects of immune cells on ischemic stroke and the mediating roles of metabolites - Hu, Haoxiang; Zhou, Mi; Zhao, Yunhan; Mao, Jiesheng; Yang, Xiaokai (Frontiers in Neurology, 2024)
Objective: Previous studies have not shown an association between IgD-CD24-B-cell absolute count (IgD-CD24-AC) and ischemic stroke (IS). Our study aimed to assess the causal effect of IgD-CD24-AC on IS and to explore the role of ascorbic acid 2-sulfate (AA2S) as a potential mediator.Our study was based on the largest available genome-wide association study (GWAS). Inverse variance weighting (IVW), MR-Egger, weighted median (WMN), simple mode, and weighted mode methods were used to assess causal effects, with IVW as the primary outcome. Subsequently, we further performed a two-step MR analysis to evaluate whether AA2S mediated this causal effect. In addition, several sensitivity analyses were conducted to evaluate heterogeneity, including Cochrane's Q test, the MR-Egger intercept test, the MR-PRESSO global test, and the leave-one-out analysis.Results: Using the IVW approach, the risk ratio of IgD-CD24-AC to IS was estimated to be 1.216 (95% CI = 1.079-1.371, P = 0.001). This result was supported by the WMN method (OR = 1.204, 95% CI = 1.020 -1.421, P = 0.028) and the MR-Egger method (OR = 1.177, 95% CI = 0.962 -1.442, P = 0.133). We also observed the same trend with the simple model and weighted model. Furthermore, the proportion of genetically predicted IgD-CD24-AC mediated through AA2S levels was 3.73%.Our study revealed a causal relationship between IgD-CD24-AC and IS, a small part of which was mediated by AA2S. These findings offer critical insights for developing immune-targeted therapies in the future and lay a strong foundation for advancements in precision medicine.